The Effect of the round house strategy on the achievement of physical concepts at the ninth grade in Jordan - Alsous, Rida Ali (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to clear-out the effect of the round house strategy on the achievement of physical concepts at the ninth grade. The study consisted of (48) students at the Jufa Secondary School for girls for the second semester 2018/2019, distributed randomly to two divisions in the same school, one of which was experimental and the other experimental.This study found that there was a statistically significant difference in the post-test in the students' acquisition of physical concepts at (α = 0.05) between the average performance of the experimental group studied using the circular house strategy and obtained an average of (19.70), and the control group studied in the usual way and obtained Average (14.63), in favor of the experimental group. In light of these results, the researcher recommended using the circular house strategy because of its importance in gaining physical concepts among students.In light of these results, the researcher recommended using the round house strategy and its role in acquiring physical concepts in demand
Keywords: Round House Strategy; Physical Concepts; Ninth Grade Students